2014
DOI: 10.4049/jimmunol.1301302
|View full text |Cite
|
Sign up to set email alerts
|

The Pore-Forming Toxin Listeriolysin O Is Degraded by Neutrophil Metalloproteinase-8 and Fails To Mediate Listeria monocytogenes Intracellular Survival in Neutrophils

Abstract: The pore-forming toxin listeriolysin O (LLO) is a major virulence factor secreted by the facultative intracellular pathogen Listeria monocytogenes. This toxin facilitates L. monocytogenes intracellular survival in macrophages and diverse nonphagocytic cells by disrupting the internalization vesicle, releasing the bacterium into its replicative niche, the cytosol. Neutrophils are innate immune cells that play an important role in the control of infections, yet it was unknown if LLO could confer a survival advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 95 publications
0
30
0
Order By: Relevance
“…Preparation of all MARTX Vc and MARTX Ah constructs (Kudryashova et al, 2014), PA (Wesche et al, 1998), and CDC toxins [LLO, ALO, and PLY; (Arnett et al, 2014; Glomski et al, 2002)] was published. TcdA- and TcdB-GTD constructs were expressed in Bacillus megaterium cells (provided by Dr. Lacy; Vanderbilt University) and purified as described (Chumbler et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of all MARTX Vc and MARTX Ah constructs (Kudryashova et al, 2014), PA (Wesche et al, 1998), and CDC toxins [LLO, ALO, and PLY; (Arnett et al, 2014; Glomski et al, 2002)] was published. TcdA- and TcdB-GTD constructs were expressed in Bacillus megaterium cells (provided by Dr. Lacy; Vanderbilt University) and purified as described (Chumbler et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency of escape depends upon the nature and activation status of the host cell, and can vary from phagosome to phagosome within the same cell. For example, LLO and the PLCs are less efficient in activated than resting macrophages and are unable to protect L. monocytogenes from intracellular killing in human neutrophils [108, 109]. In these examples, it appears that host cells can use various strategies to limit or even prevent vacuolar escape.…”
Section: Listeriolysin O Is An Intracellular Pore-forming Toxin With mentioning
confidence: 99%
“…Also, lysosomal cathepsin-D degrades LLO in murine fibroblasts and macrophages, limiting the efficiency of L. monocytogenes escape in cultured cells, and impacting the course of infection in a murine model of listeriosis [111]. A similar enzymatic process was recently proposed to exist in neutrophils in which the matrix metalloproteinase-8, stored in secondary granules, degrades LLO [109]. Also, the antimicrobial peptides, α -defensins, stored at high concentrations in neutrophil primary granules, inhibit LLO release from the bacterium in addition to blocking its activity [64, 65].…”
Section: Listeriolysin O Is An Intracellular Pore-forming Toxin With mentioning
confidence: 99%
“…monocytogenes internalization was shown to be significantly different when comparing MOIs of 1 and 10 amongst different studies [32]. Further, using the same approach, it was reported that the percentage of infected cells at 4 and 24 hpi depends on the MOI used to infect cells [30].…”
Section: Figure 1| Macromolecular Differences Between Cells Of Eukarymentioning
confidence: 94%